Genetical, clinical, and functional analysis of a large international cohort of patients with autosomal recessive congenital ichthyosis due to mutations in NIPAL4 - Ballin, Nadja; Haußer-Siller, Ingrid (Human mutation, 2019)
Autosomal recessive congenital ichthyosis (ARCI) belongs to a heterogeneous group of disorders of keratinization. To date, 10 genes have been identified to be causative for ARCI. NIPAL4 (Nipa-Like Domain-Containing 4) is the second most commonly mutated gene in ARCI. In this study, we present a large cohort of 101 families affected with ARCI carrying mutations in NIPAL4. We identified 16 novel mutations and increase the total number of pathogenic mutations in NIPAL4 to 34. Ultrastructural analysis of biopsies from six patients showed morphological abnormalities consistent with an ARCI EM type III. One patient with a homozygous splice site mutation, which leads to a loss of NIPAL4 mRNA, showed additional ultrastructural aberrations together with a more severe clinical phenotype. Our study gives insights into the frequency of mutations, a potential hot spot for mutations, and genotype-phenotype correlations.